Selected Areas in Cryptography 17th International Workshop, SAC 2010, Waterloo, Ontario, Canada, August 12-13, 2010, Revised Selected Papers - Biryukov, Alex.; Gong, Guang; Stinson, Douglas R.; SpringerLink (Online service) (2011)
This book constitutes the thoroughly refereed post-proceedings of the 17th Annual International Workshop on Selected Areas in Cryptography, SAC 2010, held in Waterloo, Ontario, Canada in August 2010. The 24 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 90 submissions. The papers are organized in topical sections on hash functions, stream ciphers, efficient implementations, coding and combinatorics, block ciphers, side channel attacks, and mathematical aspects.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data encryption (Computer science).; Computer software; Information systems; Computer Science; Data Encryption; Operating Systems; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Information Systems Applications (incl.Internet).